A dimensão temática da pesquisa em organização do conhecimento: Uma análise de domínio dos congressos nacionais e regionais da ISKO (Brasil, Espanha e América do Norte) - Guimarães, José Augusto Chaves [UNESP]; Dos Santos, André Ynada [UNESP]; Cândido, Gilberto Gomes [UNESP]; Pinho, Fabio Assis (My University, 2014)
This article is the result of a domain analysis of the articles published in the congresses of ISKO in Brazil, Spain and North America, aiming at identifying the themes and scientific collaboration characteristics, as an input for future studies on research trends and promoting the growth of the participation in each community. So it was characterized as an exploratory research focused on the analysis domain. The results showed that the Brazilian, North American and Iberian ISKO Chapters have been building a large space of scientific production with some convergent subjects like the epistemological questions, but also considering the regional specific ones. In this vein, the presence of researchers in the three studied academic spaces reveals a concern on establishing dialogical basis in KO research, whose main research institutions are São Paulo State University (UNESP, Brazil), University of Wisconsin Milwaukee (UWM, United States) and University Carlos III de Madrid (UC3M, Spain), which have deeply intensified their collaboration in joint publications.
The subject dimension of knowledge organization research: A domain analysis of the Brazilian, Spanish and North American ISKO chapters' conference
Keywords: Brasil; Collaboration networks; Domain analysis; Estados unidos; Iberia; ISKO; Knowledge organization; Scientific productivity